Lake Inflow Simulation Using the Coupled Water Balance Method and Xin’anjiang Model in an Ungauged Stream of Chaohu Lake Basin, China - Li, Zijun; Lei, Xiaohui; Liao, Weihong; Yang, Qingchun; Cai, Siyu; Wang, Xiaoying; Wang, Chao; Wang, Jia (Frontiers in Earth Science, 2021)
Water resources are crucial for maintaining daily life and healthy ecological environment. In order to gain a harmonious development among water resources and economic development in Lake Watershed, it is urgent to quantify the lake-inflow. However, the accurate inflow forecast is severely limited by the lack of information regarding river flow. This paper attempts to overcome these problems through coupling water balance method and the Xin’anjiang model, and applying it to Chaohu Lake Basin. Meanwhile, according to the results of the three copula functions embodying bivariate probability distribution of annual precipitation and annual highest water level, Gumbel-Hougaard method is best to select the typical hydrological years, including high inflow (2016), normal inflow (2007) and low inflow year (1978). Additionally, the calibration and verification results of the coupled model suggest that the simulation results are best in the high inflow year, followed by the normal inflow year and the low inflow year. Also, annual lake inflow simulation in normal inflow year is 19.4×108 m3, while the findings of the annual average land surface runoff of the study area is 18.9×108 m3, indicating that the coupled model have been proved to be robust in determining inflow in ungauged stream. The results of this present provides a basis for determining the appropriate management of water resources systems.